Does Democracy Still Have a Chance? Contextualizing Citizenship Education in China. Issue 1 (3rd March 2020) - Yu, Tianlong
Abstract: This paper examines the challenges and possibilities facing democratic citizenship education in China. It starts by taking on the increasing political repression under Xi's regime and how it is marginalizing or silencing democratic discourses. Then it examines the rising economically-driven populist nationalism in China, and how it complicates the democratic pursuit. Next, the paper looks into the dominant Chinese cultural tradition, Confucianism, its antidemocratic tendencies and alliance with authoritarian forces. The paper concludes with a discussion of potential ways to combat the roadblocks and resistances to democratization. It emphasizes a more nuanced understanding of both China's historical trajectories and present aspirations, seeking possibilities for democratic breakthrough. It also proposes educational and curricular reform, deconstructing official moral education and introducing cultivation in civic virtues, for example, to promote democratic citizenship.